Answer:
10
Step-by-step explanation:
Answer:
top right
Step-by-step explanation:
If you imagine yourself building with that model you can see its that one
I’m not rly sure what it means by flipping the card …. I’m assuming there’s more to this question but if it’s what I think it is the only way this equation will be true is by switching the + Symbol to - (subtraction) which would be 1-2= 3-4 since it would 1=1 making the equation true
In this problem we need to find the value of a and b. So given that t<span>he function should be in the form f(n) = an + b and we know each value of n, then out goal is to find a and b.
For getting this purpose, we need to find a system of two equations (given that we have two unknown variables)
Therefore:
(1) f(0) = a(1) + b = 18
</span>∴ a + b = 18
<span>
(2) f(1) = a(2) + b = 24
</span>∴ 2a + b = 24<span>
Solving for a and b we have:
a = 6
b = 12
Finally:
f(n) = 6n + 12</span>
Answer:
436.96
Step-by-step explanation:
Using the compoybd interest formula A=P(1+R÷N)^nt
A= Final amount 436.96
P= Initial Balance 420
r= interest rate 4%
n= number of times interest applied per time period 2
t = number of times periods elapsed 2